Pengaruh Produk, Kualitas Pelayanan, Lokasi, Promosi, dan Harga Terhadap Keputusan Pembelian Pada Pasar Swalayan Surya Jaya - Rismahendra, Muhammad Abrar; , Dra. Wafiatun Mukharomah, S.E.,M.M (2016)
This research was conducted in Karanganyar and has the purpose to analyze the influence of Product, Quality Service, Location, Promotion, and Price on purchasing decisions. This research is descriptive quantitative research using questionnaires as a means of collecting data were analyzed using SPSS data processing software. The samples were carried out using non-probability sampling through accidental sampling method, the number of respondents used was 100 respondents. The analytical tool used in the research is to test the instrument, the classical assumption test, data analysis (Regression Analysis, t test, F test and coefficient of determination). Data analysis results can be obtained, there is a positive and significant influence between Products, Quality Service, Location, Promotion and Price in the purchasing decision at the supermarket Surya Jaya in Karanganyar. And there is the influence of the Product, Service Quality, location, promotion, and price simultaneously towards buying decision. The survey results revealed bahwaProduk is a variable that gives the most influence on purchase decision.